Faktor-faktor yang Berhubungan dengan Kejadian Demam Berdarah Dengue di Kelurahan Sesetan Kecamatan Denpasar Selatan Kota Denpasar Tahun 2022 - I Gusti Ayu Made Aryasih; Ni Kadek Nila Trismayanti; M. Choirul Hadi; Ni Made Marwati (Poltekkes Kemenkes Denpasar, 2022)
Dengue Hemorrhagic Fever is an infectious disease that is transmitted through the bite of the Aedes aegypti mosquito. The purpose of this study was to determine the factors associated with the incidence of Dengue Hemorrhagic Fever in Sesetan Village, South Denpasar District, Denpasar City in 2022. This type of research used a cross sectional approach. The sample in this study was 99 respondents who were selected by simple random sampling, analyzed by Chi Square and CC calculations. Based on the Chi Square test of knowledge, the value of p = 0.001 0.05, CC value = 0.354, PSN 4M Plus p = 0.003 0.05, CC value = 0.328, health promotion p = 0.000 0.05, CC value = 0.378 and the presence of p larvae = 0.000 0.05 CC value = 0.488. The conclusion of this study is that there is a relationship between knowledge factors, PSN 4M Plus, health promotion services and the presence of larvae associated the incidence of Dengue Hemorrhagic Fever in Sesetan Village, South Denpasar District, Denpasar City in 2022. Suggestions that can be submitted are for the community, especially housewives to increase PSN 4M Plus and reduces the presence of larvae.